A methods engineering study on Cychris Trading Corporation - Craig, Angelica; Ty, Jeremiah D.; Vergara, Erizelle (Diliman, Quezon City College of Engineering, 2005)
Cychris Trading Corporation is a garments manufacturing firm that has recently pushed for reorganization and formalization of its production line. In line with this, a Methods Engineering Study was conducted to diagnose and set standards for the company. During the study, it was deemed that, indeed a number of the problems facing Cychris were rooted in the disorganized and structure of the company. The records, standards and raw material storage systems of the company were seen to be prime contributors to the problems of under-runs and late deliveries. Fabric damage was also singled out. It was recommended that the company pursue a computerization of its records and a reorganization of its raw material storage. Also, it was seen that an inventory system and a series of inspections down its production line were necessary.
IE 32
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Cychris Trading Corporation; Clothing trade; Systems analysis